2020
DOI: 10.1016/j.knosys.2020.105717
|View full text |Cite
|
Sign up to set email alerts
|

Vital spreaders identification in complex networks with multi-local dimension

Abstract: The important nodes identification has been an interesting problem in this issue. Several centrality measures have been proposed to solve this problem, but most of previous methods have their own limitations. To address this problem more effectively, multi-local dimension (MLD) which is based on the fractal property is proposed to identify the vital spreaders in this paper. This proposed method considers the information contained in the box and q plays a weighting coefficient for this partition information. ML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(25 citation statements)
references
References 82 publications
(63 reference statements)
0
25
0
Order By: Relevance
“…Liu et al [198] proposed a generalized weighted gravity model, called generalized mechanics model (GMM), by considering global information and local information. Wen et al [199] proposed multi-local dimension (MLD) based on the fractal property to identify vital spreaders in complex networks. MLD is considered as a more general method, such as some existing centrality metrics.…”
Section: ) Influence Maximizationmentioning
confidence: 99%
“…Liu et al [198] proposed a generalized weighted gravity model, called generalized mechanics model (GMM), by considering global information and local information. Wen et al [199] proposed multi-local dimension (MLD) based on the fractal property to identify vital spreaders in complex networks. MLD is considered as a more general method, such as some existing centrality metrics.…”
Section: ) Influence Maximizationmentioning
confidence: 99%
“…Liu et al [25] proposed a GMM model, which combines the local information and global information of the network to identify the most influential nodes in the social network. Wen et al [26] proposed multi-local dimension (MLD) method to identify the vital spreader in the social network and found that the node with low MLD value would be more important in the network. On the other hand, heuristic algorithms based on greedy mechanisms mainly include CELF [27], CELF++ [28], etc.…”
Section: Related Workmentioning
confidence: 99%
“…There is a thriving interest in the study of games, 1 which has diverse applications in areas such as communications, networking, economics, and control theory 2‐8 . Computer science and artificial intelligence (AI) are no exception.…”
Section: Introductionmentioning
confidence: 99%